Rapid production of a chimeric antibody-antigen fusion protein based on 2A-peptide cleavage and green fluorescent protein expression in CHO cells. Issue 3 (3rd April 2019) - Van der Weken, Hans; Cox, Eric; Devriendt, Bert
ABSTRACT: To enable large-scale antibody production, the creation of a stable, high producer cell line is essential. This process often takes longer than 6 months using standard limited dilution techniques and is very labor intensive. The use of a tri-cistronic vector expressing green fluorescent protein (GFP) and both antibody chains, separated by a GT2A peptide sequence, allows expression of all proteins under a single promotor in equimolar ratios. By combining the advantages of 2A peptide cleavage and single cell sorting, a chimeric antibody-antigen fusion protein that contained the variable domains of mouse IgG with a porcine IgA constant domain fused to the FedF antigen could be produced in CHO-K1 cells. After transfection, a strong correlation was found between antibody production and GFP expression (r = 0.69) using image analysis of formed monolayer patches. This enables the rapid selection of GFP-positive clones using automated image analysis for the selection of high producer clones. This vector design allowed the rapid selection of high producer clones within a time-frame of 4 weeks after transfection. The highest producing clone had a specific antibody productivity of 2.32 pg/cell/day. Concentrations of 34 mg/L were obtained using shake-flask batch culture. The produced recombinant antibody showed stable expression, binding and minimal degradation. In the future, this antibody will be assessed for its effectiveness as an oral vaccine antigen.